2019
DOI: 10.3390/en12142719
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Cost of Building Energy Renovation Measures, Considering Future Energy Production Scenarios

Abstract: A common way of calculating the life cycle cost (LCC) of building renovation measures is to approach it from the building side, where the energy system is considered by calculating the savings in the form of less bought energy. In this study a wider perspective is introduced. The LCC for three different energy renovation measures, mechanical ventilation with heat recovery and two different heat pump systems, are compared to a reference case, a building connected to the district heating system. The energy syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The cost of renovation is an important criteria for decision making and determining renovation solutions. Gustafsson [20] analyzed energy renovation measures in Sweden and showed that all renovation measures resulted in an increased life cycle cost (LCC), compared to the reference building. Firląg et al [8] analyzed nZEB solutions for heating dominated climate and showed that nZEB renovation is not yet cost optimal in Poland.…”
Section: Introductionmentioning
confidence: 99%
“…The cost of renovation is an important criteria for decision making and determining renovation solutions. Gustafsson [20] analyzed energy renovation measures in Sweden and showed that all renovation measures resulted in an increased life cycle cost (LCC), compared to the reference building. Firląg et al [8] analyzed nZEB solutions for heating dominated climate and showed that nZEB renovation is not yet cost optimal in Poland.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this paper is to present a transparent, openly accessible, adaptable framework for a sustainable renovation process covering technical environmental, economic, social, and cultural historical aspects that must be considered by the various actors during different stages of the renovation process. It has been noted many times that there is a need for practical methods to complement the strong focus on economy in decision processes aiming at sustainable solutions [3,5,6,8,24,30,37].…”
Section: Discussionmentioning
confidence: 99%
“…Malmqvist et al, on the other hand, used two indexes: external load index, including mostly energy aspects, and internal load index, based on a questionnaire about indoor environment [23]. Some authors use more standardized values, such as life cycle cost [24] or greenhouse gas (GHG) [25].…”
Section: Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, new research show that the future will belong to plus energy buildings. The study of Gustafsson [8] concentrates on building energy systems in the context of renovation. This is especially important when aiming towards the 100% share of the renewable system in the future.…”
Section: Introductionmentioning
confidence: 99%